Synthesis of antimicrobial glucosamides as bacterial quorum sensing mechanism inhibitors. Issue 3 (1st February 2017) - Biswas, Nripendra N.; Yu, Tsz Tin; Kimyon, Önder; Nizalapur, Shashidhar; Gardner, Christopher R.; Manefield, Mike; Griffith, Renate; Black, David StC.; Kumar, Naresh
Graphical abstract: Abstract: Bacteria communicate with one another and regulate their pathogenicity through a phenomenon known as quorum sensing (QS). When the bacterial colony reaches a threshold density, the QS system induces the production of virulence factors and the formation of biofilms, a powerful defence system against the host's immune responses. The glucosamine monomer has been shown to disrupt the bacterial QS system by inhibiting autoinducer (AI) signalling molecules such as the acyl-homoserine lactones (AHLs). In this study, the synthesis of acetoxy-glucosamides8, hydroxy-glucosamides9 and 3-oxo-glucosamides12 was performed via the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and N, N′ -dicyclohexylcarbodiimide (DCC) coupling methods. All of the synthesized compounds were tested against two bacterial strains, P. aeruginosa MH602 (LasI/R-type QS) and E. coli MT102 (LuxI/R-type QS), for QS inhibitory activity. The most active compound9b showed 79.1% QS inhibition against P. aeruginosa MH602 and 98.4% against E. coli MT102, while compound12b showed 64.5% inhibition against P. aeruginosa MH602 and 88.1% against E. coli MT102 strain at 2 mM concentration. The ability of the compounds to inhibit the production of the virulence factor pyocyanin and biofilm formation in the P. aeruginosa (PA14) strain was also examined. Finally, computational docking studies were performed with the LasR receptor protein.